2020
DOI: 10.2196/13852
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Digital Content-Free Speech Analysis Tool for the Measurement of Mental Health and Follow-Up for Mental Disorders: Protocol for a Case-Control Study

Abstract: Background The prevalence of mental disorders worldwide is very high. The guideline-oriented care of patients depends on early diagnosis and regular and valid evaluation of their treatment to be able to quickly intervene should the patient’s mental health deteriorate. To ensure effective treatment, the level of experience of the physician or therapist is of importance, both in the initial diagnosis and in the treatment of mental illnesses. Nevertheless, experienced physicians and psychotherapists a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
0
2
0
3
Order By: Relevance
“…Por su parte Mitra et al (2015) plantean en su estudio que las tareas de lectura y de libre expresión se comportan de manera diferente, coincidiendo con el resto de los autores en que la mejor tarea es la de libre expresión (Figueroa et al, 2020;Hashim et al, 2016;Jiang et al, 2017Jiang et al, , 2018Mitra et al, 2015;Ozdas et al, 2000;Parekh & Patil, 2017;Scherer et al, 2013Scherer et al, , 2015Subari et al, 2010;Suwannakhun & Yingthawornsuk, 2019;Tonn et al, 2020;Yingthawornsuk, 2016;Yingthawornsuk & Shiavi, 2008;Zhang et al, 2020). Esta información es de utilidad, ya que nos indica que en las evaluaciones debemos incluir, por lo menos, una tarea de libre expresión, lectura de texto y/o descripción de imágenes.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Por su parte Mitra et al (2015) plantean en su estudio que las tareas de lectura y de libre expresión se comportan de manera diferente, coincidiendo con el resto de los autores en que la mejor tarea es la de libre expresión (Figueroa et al, 2020;Hashim et al, 2016;Jiang et al, 2017Jiang et al, , 2018Mitra et al, 2015;Ozdas et al, 2000;Parekh & Patil, 2017;Scherer et al, 2013Scherer et al, , 2015Subari et al, 2010;Suwannakhun & Yingthawornsuk, 2019;Tonn et al, 2020;Yingthawornsuk, 2016;Yingthawornsuk & Shiavi, 2008;Zhang et al, 2020). Esta información es de utilidad, ya que nos indica que en las evaluaciones debemos incluir, por lo menos, una tarea de libre expresión, lectura de texto y/o descripción de imágenes.…”
Section: Discussionunclassified
“…Está bien documentado que las emociones influyen en la voz. El comportamiento suicida se ha vinculado a la depresión y, por ende, algunos investigadores están tratando de encontrar signos tempranos para ayudar a detectar la depresión a través del análisis acústico de la voz de un paciente (Tonn et al, 2020).…”
Section: Hallazgos De Voz Y Habla En Conducta Suicidaunclassified
See 1 more Smart Citation
“…Nonetheless, smartphone-based monitoring of objective data in mood disorders is a rapidly growing approach and a highly innovative research field. This is evident in a number of study protocols stating ambitions to expand and intensify research in the field [ 64 , 65 ]. Although promising, a much larger evidence base is required to fully realize the potential, as well as the risks, of these approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have begun to use automated analysis tools to profile the specific speech and language changes in FTD subtypes in more detail ( Cho, Nevler, Ash, et al, 2021 ; Nevler et al, 2019 ; Nevler, Ash, McMillan, et al 2020 ) and have identified changes such as decreased speech output and lower lexical diversity, which are common across subtypes ( Cho, Nevler, Ash, et al, 2021 ). An ongoing study analyzing digital content-free speech data, language, and tone may provide equally important insights for diagnosis and care management ( Tonn et al, 2020 ).…”
Section: Speech and Language Changes In Ftd Subtypesmentioning
confidence: 99%